Experimental and computational validation on the adsorption behaviour of quercetin and rutin on ion exchange resins - Anannya Kalita; Rabu Ranjan Changmai; Manabendra Sarma; Monali Dutta Saikia (Results in Surfaces and Interfaces)
High-purity flavonoids such as rutin and quercetin are required significantly in the pharmaceutical and food industries. These two flavonoids usually occur as mixtures in different plant resources. Also, commercially obtained rutin is contaminated with nearly 1–3% of quercetin. Herein, two ion exchange resins, Dowex 1X4 chloride and Dowex 50WX8, were evaluated for selective adsorption or enrichment of flavonoid molecules, such as quercetin and rutin, from aqueous solution. It was observed that anion exchange resin had higher adsorption selectivity for quercetin over rutin. The effect of pH analysis confirmed that a combined consequence of molecular adsorption and ion exchange mechanism had taken place under alkaline conditions (pH = 11), but under acidic conditions (pH = 3), molecular adsorption was the only process of flavonoid uptake. We carried out first principle-based density functional theory (DFT) calculations to get more insight into the nature of the interactions between adsorbate and adsorbent. The molecular electrostatic potential (MEP) maps gave an idea of the active sites by showing electron density distribution throughout the systems. The reduced density gradient (RDG) scatter plot showed significant evidence for strong ionic interactions and weak van der Waals interactions between the flavonoid molecules and the resins.